2018
DOI: 10.1177/2165079918756909
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Workplace Injuries and Violence Among Newly Licensed RNs

Abstract: Workplace injuries, such as musculoskeletal injuries, needlestick injuries, and emotional and physical violence, remain an issue in U.S. hospitals. To develop meaningful safety programs, it is important to identify workplace factors that contribute to injuries. This study explored factors that affect injuries in a sample of newly licensed registered nurses (NLRNs) in Florida. Regressions were run on models in which the dependent variable was the degree to which the respondent had experienced needlesticks, work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
4
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
3
4
0
6
Order By: Relevance
“…The highest risk of aggressive acts was reported during afternoon and evening shifts, which is in line with the findings of some studies [37] but not all studies, because the literature also contains discordant findings [45,46,48]. The increased risks of assault may be explained, in part, by considering the types of patients admitted to the AOU Città della Salute and by analysing organizational factors.…”
Section: Discussionsupporting
confidence: 76%
“…The highest risk of aggressive acts was reported during afternoon and evening shifts, which is in line with the findings of some studies [37] but not all studies, because the literature also contains discordant findings [45,46,48]. The increased risks of assault may be explained, in part, by considering the types of patients admitted to the AOU Città della Salute and by analysing organizational factors.…”
Section: Discussionsupporting
confidence: 76%
“…It is important to emphasize that nurses who worked voluntary overtime were found to have a higher likelihood of occupational injuries than those who did not, indicating substantial exposure to potential injuries. Several studies have also reported that working overtime significantly increased the risk of injuries in nurses (Stimpfel, Brewer, & Kovner, 2015;Unruh & Asi, 2018;Wu et al, 2018 working more voluntary overtime had higher levels of job satisfaction, but they also had higher levels of occupational injuries. Therefore, it is important to monitor both their work hours and overtime and then implement managerial strategies to prevent such occupational injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Un recorrido entre las numerosas evidencias científicas publicadas en la literatura reciente muestra un perfil de accidentalidad en profesionales y técnicos de la enfermería , muy variado, en los que destacan los siguientes : exposición accidental percutánea y mucocutánea a sangre y otros fluidos biológicos potencialmente infecciosos; lesiones por sobreesfuerzos físicos; resbalones y caídas; lesiones por violencia; traumas físicos por contacto con fuentes de energía; quemaduras térmicas o químicas; asfixia y lesiones por contacto accidental con agentes químicos tóxicos (2)(3)(4)(5)(6)(7)(8)(9). El accidente que continua observándose con la mayor prevalencia en enfermeras es el contacto percutáneo a sangre y otros fluidos biológicos ( pinchazos, cortaduras y laceraciones, con agujas y objetos punzo cortantes), seguido de contacto muco-cutáneo ( salpicaduras y splash de sangre o fluidos biológicos en membranas mucosas y piel no intacta); las lesiones musculo esqueléticas por sobre esfuerzo en la asistencia de pacientes, lesiones por resbalones , tropiezos y caídas y violencia verbal y física ocupan frecuencias que engrosan la tasa de accidentalidad en las enfermeras (2,(4)(5)(8)(9)(10).…”
unclassified
“…En efecto, el sobre esfuerzo físico es un evento frecuentemente reportado en la accidentalidad en enfermeras como causa de lesiones y enfermedades ocupacionales (6-7). Accidentes frecuentes son también las caídas, resbalones y tropiezos que pueden ser la causa de esguinces, distensiones y desgarros musculares en las enfermeras, citándose el esfuerzo excesivo como uno de los factores determinantes (6)(7)9). Dentro de este panorama, un riesgo que genera gran preocupación en el ámbito de la asistencia sanitaria, es la violencia, problemática que en los últimos años va en aumento considerable en los trabajadores de la salud en todo el mundo.…”
unclassified
See 1 more Smart Citation